The Relationship between Learning Style and Quantitative/Qualitative Information Recall Performance - A.B.M Abdullah; Jerry Ligon (UUM Press, 2006)
This study examined the ability of individuals to recall qualitative or quantitative information contained in reading passages. The subjects' scores on the Kolb Learning Style Inventory (KLSI) were analyzed to determine if an individual's learning style preference affected his/her information recall performance. Demographic variables, including age, sex, grade level, employment status and length, and ethnicity were also included in the analysis. One-way ANOVA analysis was conducted to test two proposed hypotheses. Results indicated that there was significant relationship between individuals learning styles and their ability to recall qualitative information. However, for the quantitative information the results were inconclusive. Regression analysis also indicated that there was a significant relationship between the type of information recalled and recall performance. In addition to information type (qualitative/quantitative), the abstract-to-concrete AC-CE dimension score of the KLSI was also found to have significant impact on information recall performance.